ISOLATION AND IDENTIFICATION OF RINDERPEST VIRUS FROM AN OUTBREAK IN DEERS - M.Odisho, S. (The Iraqi Journal of Veterinary Medicine, 1994)
An outbreak of rinderpest virus infection diagnosed clinically in Muvlon and Dama deers at Roathat, Al-Maha Fenced Deers Farm Deers Farm in Al-Doura City Baghdad-Iraq. The virus was isolated from mesenteric lymph nodes and kidneys of the infected animals. Some of the postmortum changes of the suddenly died animals showed bloody diarrhea and congestion of the intestine, beside necrosis of the lower lips and gums. The isolated virus was indentified by the following methods: agar gel diffusion, indirect immunofluorescent technique and neutralization test using rabbit antirinderpest serum as reference.